What microglia depletion approaches tell us about the role of microglia on synaptic function and behavior - Basilico, Bernadette; Ferrucci, Laura; Khan, Azka; Di Angelantonio, Silvia; Ragozzino, Davide; Reverte, Ingrid (Frontiers in Cellular Neuroscience, 2022)
Microglia are dynamic cells, constantly surveying their surroundings and interacting with neurons and synapses. Indeed, a wealth of knowledge has revealed a critical role of microglia in modulating synaptic transmission and plasticity in the developing brain. In the past decade, novel pharmacological and genetic strategies have allowed the acute removal of microglia, opening the possibility to explore and understand the role of microglia also in the adult brain. In this review, we summarized and discussed the contribution of microglia depletion strategies to the current understanding of the role of microglia on synaptic function, learning and memory, and behaviour both in physiological and pathological conditions. We first described the available microglia depletion methods highlighting their main strengths and weaknesses. We then reviewed the impact of microglia depletion on structural and functional synaptic plasticity. Next, we focused our analysis on the effects of microglia depletion on behaviour, including general locomotor activity, sensory perception, motor function, sociability, learning and memory both in healthy animals and animal models of disease. Finally, we integrated the findings from the reviewed studies and discussed the emerging roles of microglia on the maintenance of synaptic function, learning, memory strength and forgetfulness, and the implications of microglia depletion in models of brain disease.